Obtaining optimal structural data from X-ray powder diffraction using the Rietveld method. Issue 4 (27th August 2014) - Liu, Shanke; Li, He; Liu, Jianming
<x content-type="archive" xml:space="preserve">Abstract</x> Diffraction data of calcite were collected using a conventional Bragg–Brentano diffractometer, which is a convenient, low-cost, and highly popular in-house instrument, and its crystal structure was refined by the Rietveld method. This paper shows how one treats preferred orientation and how different refinement strategies affect the accuracy of the result.